Changes in cerebral tissue perfusion during the first 48 hours of ischaemic stroke: relation to clinical outcome. Issue 1 (July 1996) - Baird, A E; Austin, M C; McKay, W J; Donnan, G A
Abstract : BACKGROUND--One major therapeutic strategy to minimise the extent of infarction after ischaemic stroke is to improve early reperfusion using thrombolytic agents. However, reperfusion may be hazardous and the period during which reperfusion may have a beneficial effect on tissue and clinical outcome is not known. METHODS--Fifty three patients were studied with serial cerebral perfusion (99mTcHMPAO SPECT) during the first 48 hours of ischaemic stroke to determine if changes in tissue perfusion during this time were prognostically significant. Single and multiple linear regression non-parametric analyses were used to include other factors during the same period which may influence outcome. RESULTS--In univariate analysis age, neurological score at admission, SPECT perfusion defect size in the first 24 hours, and percentage change in cerebral tissue perfusion at 24-48 hours (all P < 0.01) correlated significantly with the Barthel score at three months. In multiple linear regression analysis only age (P < 0.01) and percentage change in cerebral tissue perfusion at 24-48 hours (P < 0.01) provided independent prognostic information at three months. CONCLUSIONS--Changes in cerebral tissue perfusion during the first 48 hours of ischaemic stroke are significant outcome predictors and therapeutic effort aimed at increasing perfusion during this period seem to be justified.